Implementasi Model Pembelajaran Index Card Match untuk Meningkatkan Partsipasi Siswa pada Pembelajaran Tematik Kelas 3 (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The Index Card Match learning model is an active and enjoyable strategy that enhances student involvement in learning activities. This study aims to analyze the implementation of the Index Card Match model in increasing student participation in thematic learning for 3rd-grade elementary school students. The research used a qualitative method with a descriptive approach. The results showed that the Index Card Match model effectively increased student activity in the learning process through paired card matching activities involving questions and answers. Additionally, this model fosters a fun and interactive classroom environment that encourages students to be more confident and expressive. Therefore, the Index Card Match model is effective in boosting student participation and offers teachers an alternative to deliver meaningful and engaging learning experiences.